Quaerens = searchings = paghahanap Filipino essays in medieval studies - Ocampo, Ma. Liza Ruth A.; Miroy, Jovino G. (Manila UST Publishing House, 2008)
"This initial collection of Filipino Papers in Medieval studies proves that there are still some of us in Filipino letters who believe in the value of reading the Ancient texts and reading them slowly. It also demonstrates that we have been doing Medieval Studies for quite some time. Legend has it that Horacio de la Costa was a great advocate of Medieval Studies, and has made sure that libraries at the Ateneo de Manila be well stocked with sources on the Middle Ages. It will take another set of studies to document the beginnings of Medieval Studies in our country and to outline the contours of its development. For now, we offer these heretofore isolated forays into Medieval Studies in order to provide readers a cornucopia of essays that they can use either in their persona, explorations or in their history, philosophy, theology, and literature classes. These essays are not the apogee of Medieval Studies in the Philippines. It is prima facie evidence that Medieval Studies has been done and is being done on our intellectual landscape."--Back cover.
The medieval ages / Jose S. Arcilla -- The basics of indissolubility of marriage in the Decretum Gratiani / Adolfo N. Dacanay -- Metrum 8 in Book 2 of Boethius' Consolation Philosophiae / Paul A. Dumol -- Mula sa agos ng kagalakan : isang pagbasa sa Proslogion ni San Anselmo / Jovino G. Miroy -- Man's definition in Thomas Aquinas's De Unitate Intellectus Contra Averoistas : some doctrinal and historical considerations / Ma. Liza Ruth A. Ocampo -- St. Thomas Aquinas and the disputed Question De Immortalitate Animae / Roque L. Reyes -- Re-reading St. Bonaventure and environmental ethics / Ramon Rafael L. Dolor -- On the descent into darkness found in Dante, Bergman, and Coppola / Ralph A. Acuna -- Ang kahalagahan ng Proslogion sa kasaysayan ng teyismo / Tomas G. Rosario -- The dynamics of state and church relation in Marsilius de Padua's political thought / Henry Francis B. Espiritu -- William of Ockham on the nature of power : contemporary reflections on a medieval conception / Jose Ranilo B. Hermida -- Why is there evil in the world? : where does it come from? / Manuel M. Tejido -- The medieval ritual language of worship / Anscar J. Chupungco.
Keywords: Literature, Medieval -- History and criticism; Medievalism; Philippine essays (English) -- Collections